Handel's Orlando Pierre Audi (stage director), Réné Jacobs (conductor) - With Bejun Mehta (Orlando), Sophie Karthäuser (Angelica), Kristina Hammarström (Medoro)... - Handel, George Frideric (Wahoo Production, Opéra Comique, 2011)
Réné Jacobs reinvents Handel's Orlando for the 21st century with the help of the young period instrument ensemble B'Rock and a brilliant cast of soloists led by Bejun Mehta as the title hero and Sophie Karthäuser as his adored Angelica. The 1732 Orlando is one of the most groundbreaking and atypical works of Handel's uvre. Orlando stretches the opera seria form to its limits, creating characters that defy the roles of the genre's stock characters and featuring an incredibly innovative mad scene the like of which had never before been seen. Setting an older libretto by Carlo Sigismondo Capece, the opera's plot centers around four star-crossed lovers... Orlando loves Angelica, who loves Medoro, who is loved by Dorinda. Enraged when he discovers Angelica's feelings for Medoro, Orlando begins pursuing the two lovers, only to be hindered time and again by the sorcerer Zoroastro (one of the most beautiful bass roles Handel ever composed!). Photo: © Bernd Uhlig
Keywords: opera; Webcast; Internet videos; Vidéos sur Internet